(untitled) (Historia, 2021)
A particularly sensitive issue, which is gaining prominence in South Africa, is the redistribution of land and claims made by various groups to land, which they were to surrender after 1913 and even earlier. During the period 1960 to 1983, some 3,5 million South Africans were affected by the resettlement policy of former apartheid governments. To address this situation, the Reconstruction and Development Plan make provision for the establishment and implementation of a national land redistribution plan to address effectively the injustices of forced removals and the historical denial of access to land. A striking example of injustices suffered due to forced removals in the North West Province, is that of the Bakwena ba Mogopa. This article deals briefly with the reasons of the forced removal, the execution of the removal process and attempts made by the Bakwena to resist and focuses on the following: Social consequences; Economic consequences; Consequences regarding the internal political organisation of the Bakwena; and consequences regarding infrastructure.